Exploring family caregiver challenges in caring for patients with COVID-19 in intensive care units - Najafi Ghezeljeh, Tahereh; Rezaei, Masoud; Keyvanloo Shahrestanaki, Sahar; Sheikh Milani, Arezoo (Frontiers in Public Health, 2023)
Background Families of individuals hospitalized in an intensive care unit (ICU) with severe illnesses, such as COVID-19, are experiencing a range of physical and emotional stressors. Identifying the challenges faced by family members and providing support to loved ones battling life-threatening diseases can lead to improved treatment and care for the said family members in a healthcare setting. Aim The current study was conducted to explore and understand the experiences of family caregivers caring for their loved ones battling COVID-19 in an ICU. Methods This descriptive qualitative study was conducted from January 2021 to February 2022, based on the experiences of 12 family caregivers of patients with COVID-19 hospitalized in the ICU. Data collection was conducted through purposeful sampling using semi-structured interviews. MAXQDA10 software was used for data management, and conventional content analysis was used for qualitative data analysis. Results The present study conducted interviews with caregivers to understand their experiences while caring for a loved one in an ICU. Three main themes emerged from the analysis of these interviews: hardship of care trajectory, pre-loss mourning, and contributing factors in resolving family health crises. The first theme, the hardship of care trajectories, encompasses categories such as immersion in the unknown, lack of care facilities, negligence in care, neglect of families by healthcare providers, self-ignorance, and perceived stigma. The second these was pre-loss mourning that included some categories such as emotional and psychological turmoil, witnessing the exhaustion of loved ones, separation suffering, the fearing of loss, anticipatory grief, blame related to the disease causative agents, and perceived helplessness and despair. The third theme was contributing factors in resolving family health crises that included categories of the critical role of family caregivers in health engagement, the role of healthcare professionals in health engagement, and the role of interpersonal factors in health engagement. A total of 80 subcategories were also obtained based on the experiences of the family caregivers. Conclusion This study's findings indicate that families can play an important role in resolving their loved ones' health problems in life-threatening situations such as the COVID-19 pandemic. Moreover, healthcare providers must recognize and prioritize family-based care and trust the families' ability to effectively manage health crises. Healthcare providers should also be attentive to the needs of both the patient and their family members.